A intervenção social do terceiro setor no contexto do neoliberalismo : o fetiche da participação democrática e da solidariedade voluntária - Piloni, Thiago (2010)
This thesis critically analyses the third sector, not as an isolated event, but as a phenomenon associated to the current restructuring of capitalism in the new neoliberal order. It examines important political and ideological theories such as liberalism and social democracy, and aims to delineate the role of the State and the boundaries of social policy in times of neoliberalism. Based on a study of the neoliberal leap in Brazil and worldwide, the research (documentary and bibliographic) seeks to demystify promises of the so-called third sector. For this purpose, the marxist tradition and the gramscian view of the civil society are pillars